A sigma 1 region important for hemagglutination by serotype 3 reovirus strains. - Dermody, T S (1990)
Hemagglutination (HA) by the mammalian reoviruses is mediated by interactions between the viral sigma 1 protein and sialoglycoproteins on the erythrocyte surface. Three serotype 3 (T3) reovirus strains were identified that do not agglutinate either bovine or type O human erythrocytes (HA negative): T3 clone 43 (T3C43), T3 clone 44 (T3C44), and T3 clone 84 (T3C84). These three strains also showed a diminished capacity to bind the major erythrocyte sialoglycoprotein, glycophorin, in an enzyme-linked immunosorbent assay. To determine the molecular basis for these findings, we examined the deduced sigma 1 amino acid sequences of the three HA-negative T3 strains and four HA-positive T3 strains. The limited number of sequence differences in the sigma 1 proteins of these seven strains allowed us to identify single unique amino acid residues in each of the HA-negative strains (aspartate 198 in T3C43, leucine 204 in T3C44, and tryptophan 202 in T3C84) that cluster within a discrete region of the sigma 1 tail. The identification of sigma 1 residues important for HA and glycophorin binding suggests that tail-forming sequences are exposed on the virion surface, where they interact with carbohydrate residues on the surface of cells.